Antibiotic-loaded cement spacer for treatment of Klebsiella infected total hip and knee arthroplasty - Barjaktarović, Radoslav; Radoičić, Dragan; Mitković, Milorad (Vojnosanitetski pregled, 2014)
Background/Aim. Infection following total hip arthroplasty (THA) or total knee arthoplasty (TKA) may have devastating consequences. Some bacterial strains are often encountered as agents of these infections, others occur less frequently but are sometimes burdened with more severe complications. Klebsiella spp. are uncommon causes of THA or TKA infection. The aim of this study was to identify an effective treatment algorithm for multidrug resistant Klebsiella spp. caused THA or TKA infections. Methods. During the 3-year period, from January 1 2009 to December 31 2011, we registered and treated 5 patients with THA or TKA multidrug resistant Klebsiella spp. caused infection. All the patients were primarily operated in other institutions, and were admitted in our clinic after the onset of infection symptoms. In three of the cases Klebsiella infection was complicated by additional infection (Staphyloccocus aureus, Pseudomonas aeruginosa and Serratia marscescens). In 3 of the cases we performed revision arthroplasty after double exchange of antibiotic-loaded articulating cement spacer, and in 2 of the cases the standard two-stage revision approach with one antibiotic cement spacer exchange was applied. Results. The mean length of follow-up after reimplantation surgery was 17.1 months (range 2–31 months). One patient died 2 months after the final reimplantation procedure. The initial Klebsiella infection was eradicated in all the patients. At the end follow-up after definitive reimplantation, the patients had no clinical, laboratory or microbiological parameters positive for active infection. Conclusion. According to our experience with multidrug-resistant Klebsiella TKA/THA infections, two-stage approach, in some cases with double articulating cement spacer exchange prior to definitive reimplantation, is the most effective treatment option.